Experimental study on energy balance of different parameters in diesel methanol dual fuel engine. (August 2019) - Ma, Baodong; Yao, Anren; Yao, Chunde; Wang, Bin; Gao, Jian; Chen, Chao; Wu, Taoyang
Highlights: Parameter study on DMDF engine's energy balance was conducted. The S R keeps decreasing as engine load goes higher. Intake air temperature at 35–65 °C obviously affect DMDF engine thermal efficiency. Increasing cooling water temperature and methanol temperature can reduce S R . Thermal efficiency is not affected by S R while air temperature over 65 °C. Abstract: Based on the first law of thermodynamics, this paper presents the experimental results of parameter study on energy balance of a diesel methanol dual fuel (DMDF) engine including load characteristic tests for both pure diesel (D) mode and DMDF mode and comparison of energy flow conversion under different load ratios. The results show that replacement ratio keeps decreasing with load increases. In addition, operating parameters, including cooling water temperature, intake air temperature and methanol temperature, were investigated to explore their effects on energy flow distribution in DMDF engine. The results show that increasing intake air temperature has the most important effect on reducing DMDF engine' s replacement ratio. Besides that, higher cooling water temperature and methanol temperature also contribute to improving DMDF engine's thermodynamics performance. All these phenomena can be explained by the energy flow transformation when switching to DMDF combustion. On the basis of the above analysis results, some feasible measurements are proposed to further improve DMDF engine's thermodynamic behavior.